Creep behavior of the composites made from creep behavior of the composites made from waste materials of OCC recycling mills - Hamd Unesi kord khalili (Regional Information Center for Science and Technology (RICeST), 2011)
The purpose of this study was to investigate effects of different loading levels and addition of urea formaldehyde and polyethylene on the creep behavior of composites made from wastes of OCC recycling mills. The composites manufactured by hot press method and three-point bending test performed before creep test. In general, the results showed positive effects of additive materials such as urea formaldehyde and polyethylene on the creep behavior of the composites. While adding UF and PE decreased primary and final creep as well as return deformation percentage of the composites.  Also the obtained results indicated that remaining creep had higher sensitivity to loading levels compared to primary and final creep. Also the increase of the load levels from 20% to 30% led to an increase in creep content of the composites.